Implementasi Pendidikan Berbasis Literasi Di Lembaga Pendidikan Islam - Rusmadi (STAI Siliwangi Bandung, 2017)
In educational institutions in learning activities, literacy skills are important skills that students must possess. Literacy skills are needed to master a variety of subjects. In order for the student to achieve the objectives of the subject (which consists of the domain of knowledge, skills, and attitudes) they must have literacy skills. Therefore, it appears that literacy ability is not limited to cognitive ability, but the ability is more complex because it includes social aspects, linguistic aspects, and psychological aspects. The competencies developed in Islamic educational institutions based on alliteration focused on the cognitive and knowledge aspects and affective or behavioral aspects. Which includes 1) Knowledge of students about Islam 2) Implementation of the practice of worship and amaliyah. 3) Observing the soul of religion or good morals everyday or their personality. 4) Writing and public speaking skills.